2016
DOI: 10.3892/or.2016.5026
|View full text |Cite
|
Sign up to set email alerts
|

HBx-induced miR-21 suppresses cell apoptosis in hepatocellular carcinoma by targeting interleukin-12

Abstract: Abstract. Hepatitis B virus (HBV) X protein (HBx) plays a key role in the initiation and progression of HBV infection-induced hepatocellular carcinoma (HCC). Oncogenic microRNA-21 (miR-21) can be modulated by HBx protein in HCC. However, critical regulator genes in the pathway of HBx-induced miR-21 in HCC remain unclear. This study aimed to investigate the role of HBx-induced miR-21 in the apoptosis of HCC cells. In the study, interleukin-12 (IL-12) was demonstrated as a direct target of miR-21 by dual-lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Some small RNAs could be induced or exploited by viruses to favor the viral infection and persistence by attenuating the immune response, ceasing cell apoptosis, and promoting cell growth [52][53][54]. Interestingly, this strategy, as employed by a virus, was observed in HSV-1 and its host interactions [55][56][57]. Based on the roles of miRNAs during HSV-1 infection, we presumed that circRNAs functioned as miRNA sponges to indirectly regulate the host transcriptional responses.…”
Section: Discussionmentioning
confidence: 99%
“…Some small RNAs could be induced or exploited by viruses to favor the viral infection and persistence by attenuating the immune response, ceasing cell apoptosis, and promoting cell growth [52][53][54]. Interestingly, this strategy, as employed by a virus, was observed in HSV-1 and its host interactions [55][56][57]. Based on the roles of miRNAs during HSV-1 infection, we presumed that circRNAs functioned as miRNA sponges to indirectly regulate the host transcriptional responses.…”
Section: Discussionmentioning
confidence: 99%
“…116 HBx-mediated miR-21 induction inhibited cell apoptosis by suppressing IL-12 and programmed cell death 4 (PDCD4), thereby promoting HCC. 117,118 miR-21-mediated PDCD4 repression indirectly activated AP-1, which increased miR-21 transcription, creating an miR-21-PDCD4-AP-1 positive feedback loop that enhances HCC migration and invasion. 119 CCL2, which is induced by myeloid-derived angiogenic endothelial progenitor cells, increased miR-21 levels through the CCR2/JNK/AP-1 signaling pathway, promoting HCC migration, invasion, and metastasis.…”
Section: Micrornas Regulate Hcc Development By Functioning As Inflammmentioning
confidence: 99%
“…In addition, IL-12 reduces the probability of cancer development in CHB, which is a common cause of death in CHB. A study indicated that microRNA-21 could inhibit expression of IL-12, thereby increasing the proliferation of HCC (Yin et al, 2016). Another study demonstrated that genetic variants in IL-12 were associated with an increased risk of HBV-related HCC (Tan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%